Stimuli responsive macroporous hydrogels for environmental and energy applications - Faezah Mustafa (2019)
Two of the greatest challenges faced in the 21st century involve providing a sufficient amount of clean water and energy. These two resources are often interrelated. Current water desalination process is known to involve large consumption of energy and are often regarded as costly. Forward osmosis (FO) process is a potential membrane technology that can desalinate water with negligible energy requirement. This research focus on the synthesis of thermal-responsive semi-interpenetrating network (semi-IPN) hydrogels as draw agent in brackish water desalination. The semi-IPN which are composed of poly(N-Isopropylacrylamide) (PNIPAm) and poly(sodium acrylate) (PSA) were prepared by free radical polymerization. The PNIPAm networks were cross-linked by N,N’-methylenebis(acrylamide) (MBA) in the presence of linear PSA. The prepared semi-IPN hydrogels were characterized for their morphologies and thermal behaviours by scanning electron microscopy and differential scanning calorimetry, respectively. In comparison with the conventional PNIPAm hydrogel, the semi-IPN hydrogel exhibited similar lower critical solution temperature (LCST). Their swelling properties, including dependence on synthesis pH, elution of PSA and water fluxes were studied in comparison with varying PSA content. Experimental data indicates that semi-IPN hydrogels allow swelling degree to reach up to 79 g/g. Furthermore, with an increase in the molecular weight of PSA, results in higher water flux and swelling ratio in concurrent with lower amount of PSA elution. Moreover, with the hydrophilicity increase, the performance of the semi-IPN hydrogels can be potentially improved.